Public Awareness and Local Culture That Influence the Engagement of Food Waste Recycling Practice in Malaysia - Izham, Sheikh Ahmad Tajuddin Mohamed; Shaari, Mariam Felani; Zaman, Nurulhusna Qamaruz (MAJ - Malaysia Architectural Journal, 2023)
Poor food waste management is increasingly becoming a global problem due to its detrimental impact on the environment. People’s knowledge, attitudes, and behaviors toward food waste is crucial as they significantly influence sustainable food waste management practices. Cultural norms and cultural differences can also influence attitudes towards food waste which is the reasons for various advancements in both developed and developing nations. Past studies have shown that habits and emotion regarding food waste and their trade-offs were also important determinants of people’s intentions to reduce food waste and their food waste behavior. In Malaysia, recycling activities are still uncommon compared to neighboring countries such as Singapore. It is believed that better awareness and knowledge of food waste management among households is the best initial step. However, a lack of innovation and comprehensive strategies to promote this awareness akin to developed countries is a problem in Malaysia resulting in low consciousness to reduce household waste through recycling. Thus, measures to promote awareness and knowledge of food waste management among households is imperative. This paper intends to investigate the factors that influence the engagement of food waste recycling practices in Malaysia. It will suggest guidelines and a new framework which could be useful for designers to comprehend or reflect on their design work with regards to food waste management.